Aortic Valve Sclerosis as an Important Predictor of Long-Term Mortality in Patients With Carotid Atheromatous Plaque Requiring Carotid Endarterectomy - Myasoedova, Veronika A.; Saccu, Claudio; Chiesa, Mattia; Songia, Paola; Alfieri, Valentina; Massaiu, Ilaria; Valerio, Vincenza; Moschetta, Donato; Gripari, Paola; Naliato, Moreno; Cavallotti, Laura; Spirito, Rita; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: A strong association between aortic valve sclerosis (AVSc), the earliest manifestation of calcific aortic valve disease, and atherosclerosis exist. The aim of the study was to evaluate the predictive capabilities of AVSc on long-term all-cause mortality, in patients requiring carotid endarterectomy (CEA). Methods and Results: 806 consecutive CEA patients were enrolled. Preoperative echocardiography was used to assess AVSc. Computed tomography angiography was applied for plaque characterization. Kaplan-Meier curves, Cox linear regression, and area under the receiving operator characteristic (AUC) curve analyses were used to evaluate the predictive capability of AVSc.: Overall, 348 of 541 patients had AVSc (64%). Age, diabetes, and estimated glomerular filtration rate (eGFR) were associated with AVSc. In the 5-year follow-up, AVSc group had a mortality rate of 16.7% while in no-AVSc group was 7.8%. Independent predictors of all-cause mortality were age, sex, eGFR, left ventricular ejection fraction, and AVSc. After adjustments, AVSc was associated with a significant increase in all-cause mortality risk (hazard ratio, HR=1.9; 95%CI:1.04-3.54; p=0.038). We stratify our cohort based on carotid atheromatous plaque-type: soft, calcified, and mixed/fibrotic. In patients with mixed/fibrotic plaques, the mortality rate of AVSc patients was 15.5% compared to 2.4% in no-AVSc patients. In this group, AVSc was associated with an increased long-term all-cause mortality risk with an adjusted HR of 12.8 (95%CI:1.71-96.35; p=0.013), and the AUC, combing eGFR and AVSc was 0.77 (p<0.001). Conclusions: Our findings indicate that AVSc together with eGFR may be used to improve long-term risk stratification of patients undergoing CEA surgery.